The Effect of Culture, Perceptions, and Beliefs on the Decision to Purchase OB Herbal Cought Syrup Among the People of Purwokerto - Prasetyo, Rizki Galih; Rachmawati, Erny; Haryanto, Totok; Purnadi, Purnadi (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
This study aims to test and analyse the influence of culture, perceptions, and beliefs on purchasing decisions for the drug OB Herbal. The study uses quantitative research methods and focuses on communities in Purwokerto. 1500 respondents were used as sample of this study, based on certain criteria at least they had purchased the “OB Herbal” cough syrup at least once. Data collection method used the distribution of the questionnaire with a Likert scale of 5 points. Data were analysed used multiple linier regression analysis by SPSS 26 application. The findings of this study found that each culture and beliefs has an effect on “OB Herbal” cough syrup purchase decision, while perceptions has no effect on “OB Herbal” cough syrup purchase decision.